VD_FINDINFO Jug / 2017 / 30 vom 18. Januar 2017 - VD Tribunal cantonal (2017)
ESCROQUERIE, ABUS DE CONFIANCE, FAUX MATÉRIEL DANS LES TITRES, MENACEDROIT PÉNAL, TENTATIVEDROIT PÉNAL | 138 ch. 1 al. 2 CP, 146 al. 1 CP, 180 al. 1 CP, 22 ad 146 CP, 251 ch. 1 CP, 10 CPP (CH)